Toxicological Effects of Pendimethalin: Behavioral Changes and LC50 Analysis in Cyprinus carpio - Rana, Inder Singh; Sharma, Sushma; Kumar, Rajinder; Verma, Jyoti (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The pre-emergent herbicide pendimethalin is a selective dinitroaniline compound that interferes with the production of microtubules, potentially contaminating groundwater. The current investigation sought to ascertain the acute toxicity levels and behavioral effects of pendimethalin (30% EC) on Cyprinus carpio. Finney's probit bioassay method estimated the lethal toxicity LC50 values for commercial-grade herbicide pendimethalin on C. carpio. This method entails fitting the data collected from experiments to a probit model, which converts the results obtained (such as mortality rates) into a normal distribution scale. It is a useful tool in toxicological research since it enables more precise estimations of the LC50. The lethal toxicity (LC50) values of pendimethalin to C. carpio exposed to 24, 48, 72 and 96-hr were determined to be 2.83µL/L, 2.59µL/L, 2.39µL/L and 2.20µL/L based on the mortality estimations. Pendimethalin-induced behavioral abnormalities in C. carpio were investigated using sublethal concentrations (i.e., 1/15th, 1/10th, and 1/5th of the 96-hour LC50 value) at intervals of 0, 7, 14, 21 and 28 days. Our research observed behavioral shifts such as reduced general activity, reduced foraging behavior, diminished schooling behavior, reduced reflex stimuli, increased opercula movements, irregular movements, mucus secretion, enhanced breathing rates and increased surface air gulping. Our studies showed that pendimethalin can produce both mortality and behavioral alterations in Cyprinus carpio, offering important insights into the pendimethalin fatal and sub-lethal effects. These results highlight how crucial it is to keep an eye on herbicide poisoning in aquatic habitats since even sub-lethal levels can have an effect on fish behavior and the general health of the ecosystem.